(untitled) (INCH : Journal of Infant and Child Healthcare, 2023)
Based on visits by pregnant women to the Sidomulyo Health Center from January to October 2018, 30% of pregnant women were found to have anemia. The purpose of this study was to determine the effect of giving fe tablets with red guava juice on hemoglobin levels. The research was conducted at the UPTD Sidomulyo Health Center in Pekanbaru for the period January-March 2019. The type of research was a quasi-experimental study with a one-group pre-test-post-test design. The study population was all pregnant women at the UPTD Sidomulyo Health Center with a sample of 15 people taken using a purposive sampling technique. The results showed that the average hemoglobin level before being given treatment was 9.75 (SD 0.69), after being given treatment it was 13.51 (SD 0.51). Data analysis using the Wilcoxon test found that there were differences in hemoglobin levels before and after being given fe tablets with red guava juice (p=0.000). This study shows that giving fe tablets with red guava juice can increase hemoglobin levels